2013
DOI: 10.1080/00140139.2013.791377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ballistic body armour and load carriage on walking patterns and perceived comfort

Abstract: This study found that soldiers should balance loads, avoiding load placement on the non-dominant side front torso, thus minimising mobility restriction and potential injury risk. Implications for armour vest design modifications can also be found in the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 13 publications
7
41
2
Order By: Relevance
“…24 Additionally, previous research has shown that increased anterior mass significantly affects end-point (foot clearance) control in healthy adults. 16,17 In this study, an increased knee abduction angle was seen around toe off in the additional mass conditions, suggesting a limb shortening strategy to increase foot clearance during swing.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…24 Additionally, previous research has shown that increased anterior mass significantly affects end-point (foot clearance) control in healthy adults. 16,17 In this study, an increased knee abduction angle was seen around toe off in the additional mass conditions, suggesting a limb shortening strategy to increase foot clearance during swing.…”
Section: Discussionmentioning
confidence: 51%
“…4,9 The results of this study suggest that with increased anterior mass, women decrease their stride length which also may decrease the time in single limb support. 11 This decrease in stride length has also been reported in healthy adult populations with the addition of anterior and asymmetrical mass 17 compared to the no added mass conditions.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…(1) Several studies have found that exercise in body armor increased the chance of injuries due to an increased ground reaction force (GRF) (e.g., Dempsey, Handcock, & Rehrer, 2014;Orr, Pope, Johnston, & Coyle, 2014;Park et al, 2013). Yet, research on the influence of a police uniform on injury prevalence is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor, Lewis, Notley, and Peoples (2012) showed that firefighters' performance on a job-related obstacle course decreased by 27% when wearing full equipment. Furthermore, research on the effects of wearing specialized body armor in the military has revealed negative effects on balance, strength, speed, mobility and physiological strain (e.g., Daanen & Koerhuis, 2003;Park et al, 2013;Tomes, Orr, & Pope, 2017). Dempsey, Handcock, and Rehrer (2013) were the first to investigate whether wearing a complete police uniform influenced job-specific task elements.…”
Section: Testing In Uniformmentioning
confidence: 99%